2020
DOI: 10.1159/000505421
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capability and Influence Factors for a New Electrocardiogram Criterion in the Diagnosis of Left Ventricular Hypertrophy in a Chinese Population

Abstract: Introduction: Based on a small sample of patients with hypertension, a few studies have reported that the newly proposed S D + SV 4 criterion for left ventricular hypertrophy (LVH) is better than traditional criteria. This study aimed to verify the diagnostic capability of the S D + SV 4 criterion in a Chinese population with or without hypertension and to analyze the factors affecting the diagnostic accuracy of LVH. Methods: A total of 248 patients with LVH or paroxysmal supraventricular tachycardia (PSVT) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Furthermore, in the literature, the comparison between the ECG and the ECHO is a common methodology for the evaluation of electrocardiographic criteria in the diagnosis of LVH. Since the publication of the Peguero-Lo Presti criterion, several studies have been carried out in this way in order to evaluate its performance, including a meta-analysis, whose results were similar to those found in our work [19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, in the literature, the comparison between the ECG and the ECHO is a common methodology for the evaluation of electrocardiographic criteria in the diagnosis of LVH. Since the publication of the Peguero-Lo Presti criterion, several studies have been carried out in this way in order to evaluate its performance, including a meta-analysis, whose results were similar to those found in our work [19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 75%
“…ECG is currently the first requirement in terms of standard recommendations for patients with hypertension owing to its widespread popularity, low cost, and high LVH diagnostic specificity. Despite the progress of innovative ECG diagnostic criteria in recent years, such as the Seamens’ Sign 27 and Peguero–Lo Presti criteria, which improved the sensitivity and accuracy of LVH diagnosis in Chinese populations, 28 the overall sensitivity of ECG diagnosis remains inadequate. In particular, many missed LVH diagnoses remain after completion of ECG examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Xia 15 et al pointed out that S D +S v4 standard is superior to Cornell standard and Sokolow–Lyon standard in diagnosing LVH; Shao 16 et al also believed that S D +S v4 standard can be more effective than Cornell standard and Sokolow–Lyon standard. The results of this study showed that the AUC value, sensitivity and specificity of the ROC curved by S D and S D +S v4 were all better than those of the ROC curved by R avL +S v3 , and S v1 +R v5 , the Cornell standard and the Sokolow–Lyon standard, suggesting that S D and S D +S v4 could be used to diagnose elderly patients with essential hypertension and LVH.…”
Section: Discussionmentioning
confidence: 99%